INCREASING THE INVESTMENT POTENTIAL IN ENSURING THE ECONOMIC GROWTH OF THE REGIONS (ON THE EXAMPLE OF THE REPUBLIC OF UZBEKISTAN) - Valiyev Bobur Batirovich (Galaxy International Interdisciplinary Research Journal, 2022)
The article is devoted to the study of scientific views on the investment potential of the regions, the assessment of the impact of investments on economic growth in the regions and the development of proposals to increase the investment potential. It calculates the influence of investments on the economic growth of regions using the coefficient of elasticity of econometric models.